2009
DOI: 10.1177/0890334409352854
|View full text |Cite
|
Sign up to set email alerts
|

Rural-Urban Differences in Breastfeeding Initiation in the United States

Abstract: Research has noted a rural disadvantage in breastfeeding initiation; however, most previous research has been based on nonrepresentative samples and has been limited in its ability to compare racial/ethnic differences in breastfeeding initiation based on residential location. This research fills this gap by examining a nationally representative sample of births using the Early Childhood Longitudinal Study-Birth Cohort (ECLS-B) to explore associations between rural-urban residence and maternal race/ethnicity on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 41 publications
5
42
1
2
Order By: Relevance
“…The conclusions reached may not be applicable to the larger Lebanese population, especially given the likely differences in breastfeeding practices among urban and rural mothers [40]. Furthermore, different factors may come into play with ill mothers and children.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions reached may not be applicable to the larger Lebanese population, especially given the likely differences in breastfeeding practices among urban and rural mothers [40]. Furthermore, different factors may come into play with ill mothers and children.…”
Section: Discussionmentioning
confidence: 99%
“…Rural–urban differences in breastfeeding initiation, exclusive breastfeeding, and duration of breastfeeding have been reported from some countries [2,14-17]. The prevalence of breastfeeding was higher in an urban setting as compared to a rural in USA and Tanzania [2,17].…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have found breastfeeding rates to be higher in urban versus rural counties (Flower et al, 2008; Li & Grummer-Strawn, 2002; Lynch, Bethel, Chowdhury, & Moore, 2011), one previous study found that among low-income women, those living in urban areas had a lower odds of breastfeeding initiation than those living in rural areas (Sparks, 2010). While IBCLC availability does not guarantee utilization of services, our finding of higher six-week breastfeeding prevalence in urban counties with IBCLCs present suggests that IBCLC services in more urban settings may be easier for low-income families to access, potentially as a result of public transportation or cultural norms.…”
Section: Discussionmentioning
confidence: 96%